Teachers’ and students’ perception of Art Integration in Icchawar Block of Sehore District - Sarkar, Shivalika; Singh, Chitra (Voices of Teachers and Teacher Educators, 2024)
Art Integrated Learning (AIL) is one of the innovative and interdisciplinary approaches in teaching various subjects which promises to inculcate 21st century skills in the students. Teachers use arts to enrich the learning experiences of students through hands on activities and to move from abstract to concrete. This paper presents the teachers’ and students’ perception of art integrated learning as a pedagogy as well as their opinion on Attendance, Training of Teachers, Time management, Art form, Learner participation, joyful learning, discipline, parent and community support and professional development. A qualitative survey was conducted to gather the opinion of the teachers and students on the abovementioned issues. The teachers taught primary classes in the Icchawar Block of Sehore District, M.P. The data analysis of the results of the survey revealed that AIL is capable of bringing a positive change in learner participation, attendance, confidence, innovation, values and cooperation. Students reported joyful learning in the AIL class and welcomed the use of games and toys. However, both teachers and students reported that to inculcate critical thinking and connections to real world, AIL strategies need to be improved. An AIL framework may be prepared which can be implemented in the Icchawar Block of Sehore district for further improvement in areas like development of critical thinking and interdisciplinary relations.